Utilization of Polyethylene Terephthalate (PET) in Asphalt Pavement: A Review - A. F., Ahmad; A. R., Razali; I. S. M., Razelan (IOP Publishing, 2017)
The quantity of plastics used throughout the world is increasing every year. Municipal solid wastes (MSW), manufacturing processes and service industries produce a lot of waste plastic materials. The increasing awareness among consumers about the environment has contributed to the concerns over disposal of generated wastes. The growing number of plastic materials every year and limited landfill conditions causes many alternatives exist for the disposal of plastic waste. This paper provides a summary of the study on the utilization of polyethylene terephthalate (PET) in road construction. Data from researcher show that PET can improve some properties of modified asphalt mixture. Having considered the economic and environmental prudent angles, utilization of PET as an additive to asphalt mixture is suitable to be used for road pavement.